PENDAMPINGAN PENGELOLAAN AKTIVITAS LABORATORIUM UNTUK MENINGKATKAN PEMAHAMAN DAN KETRAMPILAN DASAR UJI MIKROBIOLOGI SERTA PEMANFAATAN MIKROBA DALAM PENGOLAHAN MAKANAN BAGI SISWA PESERTA EKSTRAKURIKULER SCIENCE CLUB DI SMA KATOLIK SANTA MARIA SURABAYA - Sutedja, Anita Maya; Kusumawati, Netty; Nugerahani, Ira; Virly, Virly (Jurnal Abdi Insani, 2024)
Science Club is one of the extracurricular activities at Santa Maria Catholic High School Surabaya, which is a partner in community service. Community service activities aim to assist in managing laboratory activities to improve understanding and skills in basic microbiology techniques and the use of microbes in food processing for students participating in the science club. Abdimas is carried out in three stages: preparation, assistance in managing laboratory activities, and evaluation. Preparations aim to identify problems in organizing science club activities. Laboratory activity assistance includes creating teaching materials, training for science club accompanying teachers and laboratory assistants, and organizing practical activities for science club participating students. Evaluation through quizzes and questionnaires for science club participating students aims to see the achievement of community service objectives. The community service activities produced a guidebook on "Basic Microbiology Techniques" and a leaflet on "Yoghurt Fermentation" for carrying out practical activities for students participating in the science club. The training during the community service provided skills for supervising teachers and laboratory assistants in preparing and managing practical activities in the laboratory. Activities Abdimas can also improve knowledge and skills about basic microbiology techniques and the use of microbes in yogurt fermentation for students participating in the extracurricular science club. Based on questionnaire results, after participating in the laboratory activities provided, the majority of students participating in the science club (98%) having the ability to practice basic microbiological techniques and apply aseptic techniques to utilize microbes in yogurt fermentation.